Analyzing Risk Communication, Trust, Risk Perception, Negative Emotions, and Behavioral Coping Strategies During the COVID-19 Pandemic in China Using a Structural Equation Model - Gu, Junwang; He, Rong; Wu, Xuanhui; Tao, Jing; Ye, Wenhui; Wu, Chunmei (Frontiers in Public Health, 2022)
Objective: Risk communication and the degree of trust are major factors that affect the public’s behavioral coping strategies and play an important role in emergency risk management. However, the internal formation mechanism involved in the public’s psychological behavior remains unclear. This study aimed to investigate the association among risk communication, trust, risk perception, negative emotions, and behavioral coping strategies during the coronavirus disease 2019 (COVID-19) pandemic, and to identify and quantify the factors that influence public behavior. Methods: We launched an online survey through social media from April to July 2020 in China. Relevant data were elicited using a self-designed questionnaire that mainly examined respondent characteristics, risk communication, trust, risk perception, negative emotions, protective coping behavior, and excessive coping behavior in the context of the COVID-19 pandemic. A total of 735 valid responses were obtained. A structural equation model was then used to explore relationship pathways among the components. Results: The higher the degree of risk communication (β = -0.10, p < 0.05) and trust (β = -0.22, p < 0.001), the lower the public risk perception. Risk communication and trust had a direct effect on public behavioral coping strategies during the COVID-19 pandemic. The higher the level of risk communication (β = 0.14, p < 0.001) or trust (β = 0.48, p < 0.001), the more likely it was that this would encourage the public to adopt protective coping behaviors, while the public was less likely to engage in excessive coping behaviors as the degree of trust increased (β = -0.12, p < 0.01). Risk perception influenced by poor risk communication and trust generated negative emotions (β = 0.31, p < 0.001), and such negative emotions further positively influenced public behavioral coping strategies (whether protective [β = 0.09, p < 0.05] or excessive [β = 0.24, p < 0.001] behaviors). Conclusion: Risk communication, trust, risk perception, and negative emotions were significantly directly or indirectly related to public behavior. The findings provide useful information for emergency risk management and a theoretical basis for follow-up research on public coping behavior during the COVID-19 pandemic.